2015
DOI: 10.1634/theoncologist.2015-0235
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Understanding of Cervical Cancer and Screening Is the Leading Barrier to Screening Uptake in Women at Midlife in Bangladesh: Population-Based Cross-Sectional Survey

Abstract: Background. Cervical cancer (CCa) is the second most common cancer among women in Bangladesh. The uptake of CCa screening was less than 10% in areas where screening has been offered, so we investigated the awareness of CCa and CCa screening, and factors associated with women's preparedness to be screened. Methods. A nationally representative, cross-sectional survey of women aged 30-59 years was conducted in 7 districts of the 7 divisions in Bangladesh, using a multistage cluster sampling technique. Factors ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 19 publications
(19 reference statements)
4
15
0
Order By: Relevance
“…To our knowledge, only one other study, the Bangladesh Midlife Women’s Health Study (BMWHS) has been previously conducted in Bangladesh to assess women’s knowledge of cervical cancer [ 21 ]. However, the focus of the BMWHS’s research question was on cervical cancer screening and there was no assessment of awareness or acceptability of HPV vaccination presented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, only one other study, the Bangladesh Midlife Women’s Health Study (BMWHS) has been previously conducted in Bangladesh to assess women’s knowledge of cervical cancer [ 21 ]. However, the focus of the BMWHS’s research question was on cervical cancer screening and there was no assessment of awareness or acceptability of HPV vaccination presented.…”
Section: Discussionmentioning
confidence: 99%
“…Among Bangladeshi women, one previous report has documented high (81%) awareness of cervical cancer, however, the majority (74%) of these data were collected from women residing in rural areas and limited to women above the age of 30 years [ 21 ]. Additionally, in-depth knowledge on cervical cancer, such as risk factors or symptoms, was not assessed.…”
Section: Introductionmentioning
confidence: 99%
“… 18 One other previous report of Bangladeshi women has documented high (81%) awareness of cervical cancer, however, the majority (74%) of these data were collected from women residing in rural areas and limited to women above the age of 30 years; however, this study found high awareness, but did not explore willingness to vaccinate oneself or their daughters. 19 On the contrary, in another African study, 20 low awareness was related to increased willingness to vaccinate one's child, but not oneself. To our knowledge, no previous studies have been conducted to assess the knowledge of cervical cancer and HPV, and acceptance of HPV vaccination with a focus on Bangladeshi women with high educational background and high socioeconomic status.…”
Section: Introductionmentioning
confidence: 91%
“…Within Bangladeshi society, marriage at an early age and multiple births are very common. 15,20,[22][23][24] Cumulative evidence indicates that women who have their first full-term pregnancy at 17 years or younger are more likely to develop cervical cancer as compared with those who have their first full-time pregnancy at 25 years or older. 25 Women who have multiple full term pregnancies are more likely to be exposed to more frequent and unprotected intercourse, leading to higher chances of HPV infection.…”
Section: Risk Factors Associated With Cervical Cancer In Bangladeshmentioning
confidence: 99%